The nature and role of α-MnO2 nanowires in the photocatalytic degradation of the antibiotic tetracycline. (2022) - Alinda Shaly, A.; Hannah Priya, G.; Matharasi, A.; Surya Prabha, A.; Mary Linet, J.
Abstract: Manganese dioxide (MnO2 ) is a magnetic material that finds use in the manufacture of dry cell batteries, supercapacitors, electronic circuitry, beverage cans, pesticides, fungicides, glass and pottery. MnO2 also restores the hydrosphere by improving the nature of water. Some expired antibiotics can easily intoxicate water and cause serious health issues. Hence antibiotic degradation and water purification have become essential. This report elucidates the preparation of α-MnO2 nanowires, the inferences obtained from its characterization and its application in the photocatalytic degradation of the antibiotic tetracycline. A facile hydrothermal route was employed to generate the desired α-MnO2 nanowires. The examination of its crystalline features by XRD revealed narrow crystallites with widths of around 19 nm. FTIR assessment authenticated the chemical fingerprint of the α-MnO2 sample. Bundles of α-MnO2 nanowires were visible from the pictorial views rendered by HR-SEM. A most appreciable optical band gap of about 0.99 eV was computed for α-MnO2 from the UV–Vis test. The photocatalytic application of α-MnO2 nanowires in the degradation of the antibiotic tetracycline was also studied. Hydrothermally obtained α-MnO2 nanowires were found to be efficient in degrading tetracycline.